1999
DOI: 10.1146/annurev.fluid.31.1.125
|View full text |Cite
|
Sign up to set email alerts
|

Computational Fluid Dynamics of Whole-Body Aircraft

Abstract: ▪ Abstract  The current state of the art in computational aerodynamics for whole-body aircraft flowfield simulations is described. Recent advances in geometry modeling, surface and volume grid generation, and flow simulation algorithms have led to accurate flowfield predictions for increasingly complex and realistic configurations. As a result, computational aerodynamics has emerged as a crucial enabling technology for the design and development of flight vehicles. Examples illustrating the current capability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 47 publications
0
25
0
Order By: Relevance
“…Growing computer power and development of reliable numerical techniques made it possible to obtain more detailed data from numerical modeling. Currently the flow field around an entire aircraft configuration can be modeled numerically based on inviscid and viscous models (Agarwal, 1999). Utilizing the Euler equations allows to capture the global flow structure, but because viscosity is neglected it cannot predict separation related to viscous-inviscid interaction (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Growing computer power and development of reliable numerical techniques made it possible to obtain more detailed data from numerical modeling. Currently the flow field around an entire aircraft configuration can be modeled numerically based on inviscid and viscous models (Agarwal, 1999). Utilizing the Euler equations allows to capture the global flow structure, but because viscosity is neglected it cannot predict separation related to viscous-inviscid interaction (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Relation (19) shows that the wavelet basis can represent a function with significantly fewer degrees of freedom, while still retaining an accuracy O(ǫ). However, in order to realize the benefits of wavelet compression, we need to be able to reconstruct u ≥ (p) from the subset N (ǫ) ⊂ N of significant grid points.…”
Section: Grid Adaptationmentioning
confidence: 99%
“…In the explicit approach considered here the surface is approximated explicitly using Delaunay triangulation and Voronoi diagrams. This approach has been popular in computer graphics [16,17], climate modelling [18] and aeronautical engineering [19]. In the implicit approach [20] the surface is first embedded in a higher dimensional computational space (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The participants were also requested to quantify the computational complexity of their codes: it was found that, depending on the inviscid flow model used, VII codes were one to two orders of magnitude cheaper than Navier-Stokes codes. The latter codes required 10 6 -10 7 floating-point operations per grid point; a price tag that is still representative for today's Navier-Stokes codes, as can be inferred from the review data presented by Agarwal [62].…”
Section: Application To Transonic Airfoil Flowmentioning
confidence: 99%